A microarray assessment of the modulation of human oxidative stress gene expression by rooibos and honeybush tea extracts in UVB-irradiated keratinocytes - Lana Keet; Nashia Deepnarain; Danicke Willemse; Stefan Abel; Ann Louw; Mariska Lilly (Journal of Photochemistry and Photobiology)
Ultraviolet B (UVB) radiation can lead to sunburn, premature skin aging, and skin cancer by promoting the formation of harmful reactive oxygen species (ROS) in skin cells. This study investigated the effects of rooibos and honeybush tea extracts on the expression of oxidative stress and antioxidant response genes in keratinocytes exposed to UVB. Microarray was used to investigate the expression of 84 oxidative stress response genes in response to rooibos and honeybush tea extracts and the effect of pre-exposure to extracts prior to UVB exposure was assessed. The results showed that both rooibos and honeybush tea extracts had antioxidant effects by enhancing the expression of various genes involved in the cellular defence against the damaging effects of UVB. Rooibos and honeybush extracts increased the expression of superoxide dismutases (SODs) and glutathione-related genes in skin cells associated with antioxidant enzymes. The increased expression of these genes indicates the antioxidant properties of the extracts. The tea extracts, especially honeybush, upregulated the expression of glutathione synthesis-related genes (GCLM and GCLC), which play a crucial role in maintaining cellular redox balance. Both tea extracts enhanced the expression of various genes involved in the reduction of hydrogen peroxide and lipid peroxides to prevent cellular damage, such as glutathione peroxidases (GPXs) and peroxiredoxins (PRDXs). The expression of several genes was dependent on the presence of UVB and the time after exposure. Overall, the results suggest that rooibos and honeybush tea extracts have antioxidant properties and can influence various cellular pathways involved in responding to oxidative stress and UVB radiation in skin cells. These findings support the potential benefits of these tea extracts in protecting the skin from UV-induced damage.